2017
DOI: 10.1111/cobi.12850
|View full text |Cite
|
Sign up to set email alerts
|

Toward reassessing data‐deficient species

Abstract: One in 6 species (13,465 species) on the International Union for Conservation of Nature (IUCN) Red List is classified as data deficient due to lack of information on their taxonomy, population status, or impact of threats. Despite the chance that many are at high risk of extinction, data-deficient species are typically excluded from global and local conservation priorities, as well as funding schemes. The number of data-deficient species will greatly increase as the IUCN Red List becomes more inclusive of poor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 28 publications
0
67
0
1
Order By: Relevance
“…Every sixth species currently featured on the IUCN Red List of Threatened Species is classified as data deficient. Lack of knowledge and erroneous estimates of real species status hinder effective conservation measures (Bland et al, ), and the present example highlights the severe risk facing the Danube streber, which could easily be overlooked if careful monitoring with suitable methods is not carried out. Freshwater systems are home to a very large proportion of cryptic and inconspicuous species, which are often severely threatened by human shaping of surface waters, but whose plight often remains unnoticed.…”
Section: Discussionmentioning
confidence: 90%
“…Every sixth species currently featured on the IUCN Red List of Threatened Species is classified as data deficient. Lack of knowledge and erroneous estimates of real species status hinder effective conservation measures (Bland et al, ), and the present example highlights the severe risk facing the Danube streber, which could easily be overlooked if careful monitoring with suitable methods is not carried out. Freshwater systems are home to a very large proportion of cryptic and inconspicuous species, which are often severely threatened by human shaping of surface waters, but whose plight often remains unnoticed.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, with limited funding there will undoubtedly be trade‐offs between increasing the number of plant assessments and keeping current assessments up to date (Rondinini et al ., ). A recent review of progress in achieving the Global Strategy for Plant Conservation indicated that Target 2 is unlikely to be met by 2020 (Sharrock et al ., ), highlighting the urgent need for rapid and cost‐effective assessments (Bland et al ., , ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the South African National Biodiversity Institute (SANBI, ) has nationally assessed 1987 bulbous monocots and is a good candidate for further model validation. However, obtaining suitable re‐assessment data to validate extinction risk models remains a challenge (Bland et al ., ) and such validation is in itself biased and may not estimate the true accuracy of the model (Hastie et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…The comprehensive assessment methodology prioritizes generating and updating datasets for species groups which are known to contain many threatened or near-threatened species, and there is not a bias toward specific Threats or Habitats. The number of threatened species in each Threat or Habitat class is thus a fair metric to represent the proportion of all species in those classes that are threatened (Bland et al, 2017;IUCN, 2019). Alternative metrics such as the proportion of threatened species in comprehensively assessed groups are less useful, because they misleadingly inflate the proportion of all species that are threatened, due to the preferential selection of threatened species in the comprehensive assessment process (Brummitt et al, 2015;IUCN, 2019).…”
Section: Red List Analysismentioning
confidence: 99%